The relationship between the level of development of qualitative and quantitative indicators of physical fitness of students specializing in swimming - Rayevsky D.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. This study is aimed at establishing the degree of motor skills development among students specializing in swimming, both in the aquatic environment and on land. Methods and structure of the study. The study was organized and conducted using a pedagogical experiment at the Department of Physical Education of the State University of Management located in Moscow. The analysis of the data obtained during the testing of students, including compliance with standards in water and on land, allowed us to identify key factors affecting the functional state of the body and improving the athletic performance of swimmers. Results and conclusions. The results of the study demonstrate that the manifestation of the motor abilities of student swimmers during the performance of test tasks in water and on land can be assessed as the relationship of various indicators of strength, speed and other physical parameters. Observations showed that coordination skills, a sense of rhythm and distance were manifested in the process of performing swimming and running exercises, along with strength indicators. These observations were carried out by pedagogical methods during swimming and running classes.